1997
DOI: 10.1143/jjap.36.3887
|View full text |Cite
|
Sign up to set email alerts
|

Protein Stretching II*1: Results for Carbonic Anhydrase

Abstract: The force curve measurement mode of an atomic force microscope was used to record the force required to stretch a protein molecule that was covalently sandwiched through gold-thiol bonds between a mica substrate and a silicon nitride tip, both coated with gold. In one experiment, 8 ±1 out of 20 lysyl residues of bovine carbonic anhydrase B were randomly derivatized to give free thiols, and grafted on an atomically flat gold (111) surface on mica. Force curves taken on the surface covered with protein molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, we investigated the mechanical properties of single filamin A molecules using atomic force microscopy (AFM). Recent studies have shown that AFM can detect the unfolding of proteins during extension by measuring external force in aqueous solutions [14–18]. Applying the methods used in these studies, we have found that single molecules of human endothelial filamin A are unfolded by critical external forces of various intensities, and that its unfolding is reversible; i.e.…”
Section: Introductionmentioning
confidence: 92%
“…In this study, we investigated the mechanical properties of single filamin A molecules using atomic force microscopy (AFM). Recent studies have shown that AFM can detect the unfolding of proteins during extension by measuring external force in aqueous solutions [14–18]. Applying the methods used in these studies, we have found that single molecules of human endothelial filamin A are unfolded by critical external forces of various intensities, and that its unfolding is reversible; i.e.…”
Section: Introductionmentioning
confidence: 92%
“…[4][5][6] This technique, with piconewton sensitivity and subnanometer accuracy, is powerful not only in understanding the elastic properties of random coil polymers 4 but also in exploiting the conformational changes of polymers with suprastructures. 3,[5][6][7] Some specific fingerprint information of nanomechanical properties of polymer chains has been obtained by using this method that cannot be achieved by conventional methods. For example, the SMFS spectra of 1,4-R-linked polysaccharides, such as amylose, heparin, and dextran, revealed a force-induced chair-twist boat conformational transition of individual glucopyranose rings that could be identified as a force plateau in forceextension curves.…”
Section: Introductionmentioning
confidence: 99%
“…Protein molecules are expected to undergo a tensile deformation of a bulk 3D material, at least in the initial stage of extension. Mitsui et al performed such experiments on alpha-2-macroglobulin in 1996 [8] and later on carbonic anhydrase [9] by immobilizing protein molecules on gold coated mica or silanized silicon surface through the covalent crosslinkers which were reacted with amino groups on the protein surface. After making contact with similarly modified AFM probes with the crosslinkers and forming covalently immobilizing bonds on the opposite surface of the protein molecule, the probe was pulled away from the protein substrate.…”
Section: I3 Early Studies Of Protein Stretchingmentioning
confidence: 99%